Exogenous Betaine Enhances the Protrusion Vigor of Rice Seeds under Heat Stress by Regulating Plant Hormone Signal Transduction and Its Interaction Network - Xu Mo; Jingya Qian; Peng Liu; Hongli Zeng; Guanghui Chen; Yue Wang (MDPI AG, 2022)
Rice is an important food crop. Rice seedlings are mainly composed of root, coleoptile, mesocotyl and euphylla. The elongation of coleoptile and mesocotyl promotes the emergence of rice seedlings. Therefore, analyzing the mechanism of coleoptile and mesocotyl elongation is important for the cultivation of rice varieties. Due to global warming, heat stress is threatening rice yields. Betaine plays an important role in plant resistance to heat stress; however, we lack research on its regulation mechanism of rice seed germination under heat stress. Therefore, we explored the effects of soaking seeds with betaine at different concentrations on rice seed germination under heat stress. According to the results, soaking seeds with 10 mM of betaine could effectively improve the seeds' germination potential and rate under heat stress to promote the germination of rice seeds. To clarify the mitigation mechanism of betaine in heat stress, we measured the antioxidant enzyme activity, malondialdehyde content, soluble protein content and endogenous hormone content of seed protrusion under heat stress. We constructed the cDNA library for transcriptome sequencing. According to the results, 10 mM of betaine improved the activities of the superoxide dismutase, peroxidase and catalase of seed protrusion under heat stress to reduce the malondialdehyde content and increase the soluble protein content to alleviate the effect of heat stress on rice seed germination. The detection of the endogenous hormone content showed that soaking seeds with 10 mM of betaine increased the content of gibberellin and decreased the contents of auxin and abscisic acid of seed protrusion under heat stress. According to the transcriptome analysis, betaine can induce the expressions of key genes in the biosynthesis and metabolism of auxin, abscisic acid and gibberellins in the seed coleoptile and mesocotyl elongation stage, regulate the signal transduction of three hormones and promote the germination of rice seeds under heat stress. This study revealed, for the first time, the physiological and molecular regulation mechanism of betaine promotion of seed germination under heat stress.